1991
DOI: 10.1063/1.347730
|View full text |Cite
|
Sign up to set email alerts
|

ac impedance analysis on crystalline layered and polycrystalline bismuth titanate

Abstract: Effect of bismuth oxide as a buffer layer on metal-lanthanum-substituted bismuth titanate-insulator-semiconductor structures

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0
9

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 13 publications
4
19
0
9
Order By: Relevance
“…2,3 Dielectric, optical, and optoelectronic properties of BiT are of further interest in the area of optical memories since its band gap (E g $ 3.6 eV), 4 similar to most ferroelectric perovskite oxides, lies in the visible spectrum region. As a result, dielectric [5][6][7][8][9][10][11][12][13] and optical properties [13][14][15][16][17][18][19] of BiT have been extensively investigated for decades. In addition, there has been a renewed interest in the optical properties of ferroelectric BiT as noncentrosymmetric crystal structure of room temperature BiT could trigger asymmetric electron excitation, relaxation, and scattering leading to photovoltaic effect.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Dielectric, optical, and optoelectronic properties of BiT are of further interest in the area of optical memories since its band gap (E g $ 3.6 eV), 4 similar to most ferroelectric perovskite oxides, lies in the visible spectrum region. As a result, dielectric [5][6][7][8][9][10][11][12][13] and optical properties [13][14][15][16][17][18][19] of BiT have been extensively investigated for decades. In addition, there has been a renewed interest in the optical properties of ferroelectric BiT as noncentrosymmetric crystal structure of room temperature BiT could trigger asymmetric electron excitation, relaxation, and scattering leading to photovoltaic effect.…”
Section: Introductionmentioning
confidence: 99%
“…A partir de 400ºC el mecanismo de conducción predominante cambia, quizá por la variación de la movilidad, y la energía de activación es tan sólo de 0.26 eV. Entre 500 y 650ºC el valor de 0.53 eV obtenido para el plano ab, es igual a aquel del eje c, siendo similar al encontrado en la bibliografía (17). Este hecho indica que el mecanismo de conducción es probablemente es el mismo en los dos casos y que la anisotropía de la conductividad obedece a que las capas de óxido de bismuto actúan como barreras que interrumpen el transporte de carga.…”
Section: Resultados Y Discusiónunclassified
“…Literature studies have demonstrated that impedance data related to bismuth titanates are quite complex; therefore, several semicircles are indeed expected. According to recent reports 57,58 , the first semicircle at higher frequencies can be attributed to crystalline plate, followed by plate boundary and grain boundary, respectively. Moreover, when temperature achieves 200ºC, a fourth arc appears in the modulus diagram for lower values of frequency.…”
Section: Resultsmentioning
confidence: 99%